Correlation between PD-1/PD-L1 expression and polarization in tumor-associated macrophages: A key player in tumor immunotherapy. (October 2022) - Li, Wei; Wu, Fenglei; Zhao, Shaolin; Shi, Peiqin; Wang, Shengjun; Cui, Dawei
Abstract: Tumor immunotherapy, such as PD-1/PD-L1 blockade, has shown promising clinical efficacy in patients with various types of tumors. However, the response to PD-1/PD-L1 blockade in a majority of malignancies is limited, indicating an urgent need for a deeper understanding of the mechanisms of PD-1/PD-L1 axis-mediated tumor tolerance. As the most abundant immune cells in the tumor stroma, macrophages display multiple phenotypes and functions in response to the stimuli of the tumor microenvironment. PD-1/PD-L1 has been demonstrated to be highly expressed in tumor-associated macrophages (TAMs), and TAM polarization has been shown to be important during tumor progression. In this review, we outline the relationship between TAM PD-1/PD-L1 expression and polarizations, summarize the involvement of M2 TAMs in PD-1/PD-L1-mediated T-cell exhaustion, and discuss improved approaches for overcoming PD-1/PD-L1 blockade resistance by inducing M2/M1 switching of TAMs. Graphical Abstract: ga1 Highlights: TAMs express both the receptor PD-1 and PD-L1 highly within tumor tissues. PD-1/PD-L1 axis induces TAMs to polarize toward an M2 phenotype. M2 TAMs contribute to PD-1/PD-L1 blockade resistance by inducing T-cell exclusion. M2 TAMs contribute to PD-1/PD-L1 blockade resistance by inhibiting T-cell functions. M2/M1 switching of TAMs is a promising strategy for improving tumor immunotherapy.